A contrastive study of structural and semantic features of English Yes/No questions and their Vietnamese equivalents. / Nguyễn Thị Linh; NHDKH Nguyen Dang Suu - Nguyễn, Thị Linh
The study is aimed at characteristics of English Yes- No questions and equivalent questions in Vietnamese by using Contrastive Analysis as the major method. This contrastive analysis is mainly based on different research into Yes- No questions by many English and Vietnamese linguists. In the study, English and Vietnamese Yes- No questions are analyzed in terms of its form and features to find out the similarities and differences between the questions in the two languages. These similarities and differences are clearly shown by the contrastive analysis of forms which include intonation, inversion and question particles, features of Yes/No Question content, and features of Yes/No Question in English and Vietnamese under some linguists’ points of view. It is put the focus on defining the Yes/No questions which are classified in this thesis. In the last chapter, based on the work “An Ideal Husband” by Oscar Wilder and its Vietnamese version translated by Hoàng Nguyên which contain Yes/No questions, characteristics of English and Vietnamese yes – no questions are emphasized. Furthermore, some mistakes are listed and classified. Additionally, some suggested possible solutions for the translating of English and Vietnamese Yes/No Question are withdrawn to gain an insight into how to understand the question for the daily communication and translating work.